Pain control and related factors in hospitalized patients. Issue 30 (30th July 2021) - Lin, Li-Ying; Hung, Tzu-Ching; Lai, Yen-Ho
Abstract : Abstract: Pain is a common health problem for hospitalized patients. It is necessary to understand the factors that affect patients' pain to provide individual and complete pain management. This study explored the severity and incidence of pain in hospitalized patients on the admission day, during the hospitalization, and the discharge day, and explored the predictive factors that affect the patient's pain on the discharge day. This was a retrospective study that reviewed the medical records of 73, 814 hospitalized patients from January 2016 to April 2018. The number of pain assessments was 471, 339. The incidence of pain on the discharge day of patients was significantly higher than that on the admission day. The factors that affect and predict the pain of patients on discharge day include the degree of pain on the day of admission, emotional distress on the day of discharge, disease category, gender, age, and length of stay in hospital. It shows that the higher the degree of pain on the day of admission, the higher the degree of emotional distress on the day of discharge, female patients, younger patients, longer hospitalization days, and surgical and gynecological patients have significantly higher pain levels on the day of discharge ( P < .05). This study found that the incidence of pain on the discharge day of patients was 46.5%. Previous pain level, disease category, emotional distress, gender, age, and length of hospital stay were important factors affecting patient pain on the discharge day. The influencing factors of patient pain should be fully assessed to provide individual and complete pain management, and improve patient quality of life after discharge.